Hubungan Asupan Protein dengan Kadar Ureum dan Kreatinin pada Pasien Gagal Ginjal Kronik yang Sedang Menjalani Hemodialisa di Unit Hemodialisa RS PKU Muhammadiyah Yogyakarta - Irma Ibrahim; Isti Suryani; Elza Ismail (Poltekkes Kemenkes Yogyakarta, 2017)
Background: Chronic Kidney Disease (CKD) is complication of progressive kidney disease. Kidney will lose its function to control volume and body fluids. Patient CKD will be at terminal illness in various term from 2-3 months until 30-40 years. Hemodialysis is needed for CKD stadium terminal when kidney is unable to excrete waste of metabolism, control electrolyte and fluids balance, and secrete hormone. This condition will lead cumulative Nitrogen as waste product of metabolism. Objective: To determine relation between protein intake with ureum and creatinine concentration on CKD patient with hemodialysis at Hemodialysis Unit in PKU Muhammadiyah Yogyakarta Hospital. Methods: This is a descriptive analytic research using cross sectional research design. It was held on August 2016 at PKU Muhammadiyah Yogyakarta Hospital. Population is all CKD patients with Hemodialysis. Subject is chosen by inclusion criteria: want to join research and has 30-60 years old. Results: There is no significant correlation both protein intake with ureum concentration p=0.438 and protein intake with creatinin concentration p=0.205 based on Rank Spearman test. Conclusion: There is no significant correlation both protein intake with ureum concentration, and protein intake with creatinin concentration on patients with CKD at Hemodialysis Unit in PKU Muhammadiyah Yogyakarta Hospital. Keywords: Protein intake, Ureum, Creatinin